Analysis of Viability of Core Inflation Components Based on Excluded Items in Uganda. - Munyambonera, Ezra; Mukiza, Chris Ndatira; Niyimpa, Ediga Mfite (Kabale University, 2023)
The motivation behind this study was to investigate the viability of core inflation components based on traditionally excluded items of the consumer price index in Uganda. Particularly, this was achieved through subjecting all Energy, Fuel and Utilities (E,FU) and Food crops to volatility and persistence tests. The study used time series data obtained from the Uganda Bureau of Statistics (UBOS) for the period July 2010 to June 2017 and covered all the 10 baskets monitored by UBOS. The measurement variables included volatility and persistence. In this paper, the sum of the coefficients of an AR (q) model is used as a measure of persistence. In the study, food and related items are noted to be more volatile than EFU items. Particularly tobacco leaves, peas, matooke and malewa recorded the highest volatility with a low persistence while cassava fresh, water melons, apples, ground nuts and french beans recorded the least price volatility during the study period. On the other hand, the EFU items namely petrol, diesel, paraffin, Uganda National Water (UNW), firewood and electricity recorded the least variation in prices with a high persistence during the study period. The study further indicated that inclusion of the EFU and food items found to be less volatile and highly persistent, did not yield significantly different results when comparing means of the recompiled and existing core index at 5 percent level of significance. However, the recompiled core index was more precise than the existing core index because the standard error was reduced by 7 percent. In light of the findings, this study recommends a periodical review of the core inflation components based on both volatility and persistence in order to improve estimates.